2018
DOI: 10.1214/17-aoas1091
|View full text |Cite
|
Sign up to set email alerts
|

Spatial capture–recapture with partial identity: An application to camera traps

Abstract: Camera trapping surveys frequently capture individuals whose identity is only known from a single flank. The most widely used methods for incorporating these partial identity individuals into density analyses do not use all of the partial identity capture histories, reducing precision, and while not previously recognized, introducing bias. Here, we present the spatial partial identity model (SPIM), which uses the spatial location where partial identity samples are captured to probabilistically resolve their co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 33 publications
0
86
0
Order By: Relevance
“…Fortunately, researchers have developed increasingly sophisticated camera survey designs and model advancements to improve precision of estimates, reduce sampling effort, and standardize camera survey methods (Kelly et al , Morin et al ). These include techniques for improving the identity of individuals from photos (e.g., modifying density, placement and orientation of cameras, minimizing observer bias, use of white flash cameras; Larrucea et al , Kelly et al , Mendoza et al ), more rigorous analyses of data from single‐side and hybrid camera station designs (McClintock et al , Augustine et al ), and accounting for a proportion of individuals that cannot be positively identified (Rich et al ). Collectively, these advancements should aid in developing more rigorous camera survey designs and increase confidence and utility of camera‐trapping for density estimation of small felids that may be more difficult to detect and positively identify than other larger and more recognizable species (e.g., jaguars [ Panthera onca ], leopards [ Panthera pardus ], and tigers) that are commonly used in camera‐trap research (Thornton and Pekins ).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, researchers have developed increasingly sophisticated camera survey designs and model advancements to improve precision of estimates, reduce sampling effort, and standardize camera survey methods (Kelly et al , Morin et al ). These include techniques for improving the identity of individuals from photos (e.g., modifying density, placement and orientation of cameras, minimizing observer bias, use of white flash cameras; Larrucea et al , Kelly et al , Mendoza et al ), more rigorous analyses of data from single‐side and hybrid camera station designs (McClintock et al , Augustine et al ), and accounting for a proportion of individuals that cannot be positively identified (Rich et al ). Collectively, these advancements should aid in developing more rigorous camera survey designs and increase confidence and utility of camera‐trapping for density estimation of small felids that may be more difficult to detect and positively identify than other larger and more recognizable species (e.g., jaguars [ Panthera onca ], leopards [ Panthera pardus ], and tigers) that are commonly used in camera‐trap research (Thornton and Pekins ).…”
Section: Discussionmentioning
confidence: 99%
“…However, such methods have been developed in the context of classical capture-recapture methods which ignore the spatial information inherent in most animal population sampling studies. On the other hand, for most populations we should expect the spatial location of samples to be informative about the uncertain identity of those samples (Chandler and Royle 2013, Chandler and Clark 2014, Royle 2015, Augustine et al 2016. That is, all other things being equal, samples that are in close spatial proximity to one another should more likely be of the same individual than samples that are far apart.…”
Section: Uncertain Identitymentioning
confidence: 99%
“…Camera traps provide a non‐invasive approach for detecting and monitoring wildlife that has been made more accessible through continued improvements in camera quality and cost‐efficiency, and their use in addressing fundamental ecological questions is on the rise (Burton et al., 2015; Caravaggi et al., 2017; Frey, Fisher, Burton, & Volpe, 2017). Beyond monitoring, utilization of camera traps for observational research in predator–prey ecology has exploded in recent years (Figure 1), largely due to advances in statistical techniques, such as occupancy modelling and spatial capture–recapture analysis (Augustine et al., 2018; Chandler & Royle, 2013; MacKenzie et al., 2017; Royle, Chandler, Sun, & Fuller, 2013; Sollmann et al., 2013).…”
Section: Introductionmentioning
confidence: 99%